Effect of TiO2 nanoparticles on the thermal energy storage of HITEC salt for concentrated solar power applications - Ahmad Aljaerani, Hatem; Samykano, M.; Pandey, A. K.; Said, Zafar; Sudhakar, K.; Saidur, R. (Elsevier Ltd, 2023)
Thermal energy storage materials are substantial in concentrated solar power (CSP) plants as they absorb solar thermal energy and store it to be used for electricity production. Enhancing the thermophysical properties of these materials will positively affect the efficiency of the CSP plant system and lower electricity price. This research synthesized a novel composite of Titanium Dioxide (TiO2) nanoparticles and the ternary nitrate molten salt (HITEC) at different nanoparticle concentrations. The nano-enhanced molten salt (NEMS) samples were characterized for compatibility and nanostructure analysis. Also, the thermophysical properties and thermal cycling behaviour of the NEMS samples were evaluated. The results indicate that 0.1 wt% can enhance the specific heat capacity of HITEC by 5.5 %, latent heat by 78 %, and upper working temperature by 5 %. The morphological analysis of the 0.1 wt% NEMS sample revealed a good dispersion of nanoparticles in HITEC and the formation of nanostructures. The FT-IR analysis showed the chemical stability of the nanofluid with no presence of chemical reaction between its components. The thermal cycling test of the optimum sample showed the chemical stability of the nanocomposite and the thermal cycling stability of the enhanced thermophysical properties.